Reversible Computation 5th International Conference, RC 2013, Victoria, BC, Canada, July 4-5, 2013. Proceedings - Dueck, Gerhard W.; Miller, D. Michael; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the refereed proceedings of the 5th International Conference on Reversible Computation, RC 2013, held in Victoria, BC, Canada, in July 2013. The 19 contributions presented together with one invited paper were carefully reviewed and selected from 37 submissions. The papers are organized in topical sections on physical implementation; arithmetic; programming and data structures; modelling; synthesis and optimization; and alternative technologies.
Physical implementation -- Arithmetic -- Programming and data structures -- Modelling -- Synthesis and optimization -- Alternative technologies.
Keywords: Computer science; Logic design; Software engineering; Computer software; Computer Science; Logic Design; Logics and Meanings of Programs; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Software Engineering